Peran Orang Tua Dan Guru Dalam Mendidik Anak Dalam Perspektif Islam - Azzahra Kamila Cahyani Masdar; Yova Murnika; Muhammad Fadhly; Bayu Sagara; Wismanto Wismanto (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Every child needs a proper education to improve their standard of living so that they really need an institution that is able to improve children's education in family education. The roles of parents and teachers coexist in shaping children's education. Because the main basis that parents must give to children is education. The aim of this research is that parents can realize this by guiding children's continued learning at home according to the program that the children have studied at school. Guiding children to study at home can be done by supervising and helping organize school assignments and completing the instruments and infrastructure for children to study. The research method is literature-based qualitative research. This research was conducted based on sources of information obtained by the author in the form of articles, journals, books, periodicals, etc. related to the research topic. This research examines the role of parents in educating children according to Islamic views. The results of this research show that parents have a very important role in educating their sons and daughters, because the first people they see and emulate are their parents. Meanwhile, the role of the teacher is as a successor and complement to education that begins at home. They are tasked with teaching science, both religious knowledge and world science, as well as developing the skills and potential of their students.